2022
DOI: 10.3389/fpsyg.2022.858938
|View full text |Cite
|
Sign up to set email alerts
|

Training and Transfer Effects of Combining Inhibitory Control Training With Transcutaneous Vagus Nerve Stimulation in Healthy Adults

Abstract: Inhibitory control training (ICT) is a promising method to improve individual performance of inhibitory control (IC). Recent studies have suggested transcutaneous vagus nerve stimulation (tVNS) as a novel approach to affect cognitive function owing to its ability to modulate the locus coeruleus-noradrenaline system. To examine the synergistic effects of combining ICT with tVNS, 58 young males in college were randomly assigned to four groups: ICT + tVNS, ICT + sham tVNS, sham ICT + tVNS, and sham ICT + sham tVN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(62 reference statements)
2
5
0
Order By: Relevance
“…Interestingly, we found no significant difference in signal-N2 amplitude between pre-and post-tests in the tVNS + ICT intervention group. In line with our previous results, where we found that p (respond| signal) in the SST did not differ significantly between the pre-and post-tests with tVNS + ICT intervention (Wang et al, 2022), the present finding on signal-N2 amplitude seems to demonstrate that N2 amplitude could be a marker with which to assess the ability of processing conflict signals monitored in IC. Additionally, the ceiling effect of response inhibition (Bürki et al, 2014) in the SST might be the main reason why there were no significant behavioral [p (respond| signal) ] or electrophysiological (signal-N2 amplitude) performance changes indicative of IC enhancement in the tVNS + ICT group.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, we found no significant difference in signal-N2 amplitude between pre-and post-tests in the tVNS + ICT intervention group. In line with our previous results, where we found that p (respond| signal) in the SST did not differ significantly between the pre-and post-tests with tVNS + ICT intervention (Wang et al, 2022), the present finding on signal-N2 amplitude seems to demonstrate that N2 amplitude could be a marker with which to assess the ability of processing conflict signals monitored in IC. Additionally, the ceiling effect of response inhibition (Bürki et al, 2014) in the SST might be the main reason why there were no significant behavioral [p (respond| signal) ] or electrophysiological (signal-N2 amplitude) performance changes indicative of IC enhancement in the tVNS + ICT group.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with those of previous studies on IC practice manifesting the frontal N2 latency modulation on the temporal dynamics (Millner et al, 2012), and subjects exhibited faster N2 latency after inhibition training (Schroder et al, 2020). In addition, our findings on the signal-N2 latency in the frontal region are in line with the effects of ICT on behavioral performance, whereby subjects who have undergone ICT obtained a faster stop-signal reaction time (Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the domain of executive functions, the impact of tVNS stimulation has yielded mixed results. Studying cognitive control, many studies in this domain used a combination of behavioral and biomarker or EEG recordings to determine the effect of tVNS on cognition ( Fischer et al, 2018 ; Borges et al, 2020 ; Keute et al, 2020 ; Pihlaja et al, 2020 ; Tona et al, 2020 ; Konjusha et al, 2022 ; Wang C. et al, 2022 ). Some studies found that tVNS has a positive impact on executive functions, specifically on conflict-triggered adjustment of cognitive control and executive control of action, in both behavioral and EEG data ( Fischer et al, 2018 ; Keute et al, 2020 ).…”
Section: Cognitive Effects Of Tvns On Young Healthy Participantsmentioning
confidence: 99%